Exploring the antibacterial potential of probiotics against colistin-resistant Klebsiella pneumoniae: An in vitro study - Sabrin Elkashef; Nahla Sahloul; Hagar Mowafy (Microbes and Infectious Diseases, 2025)
Background: The rise of colistin-resistant Klebsiella pneumoniae (K. pneumoniae) represents a significant challenge to antimicrobial therapy, necessitating the search for alternative or adjunctive therapies. This study aimed to assess the antibacterial effects of Lactobacillus spp. cell-free supernatants (CFS) against colistin-resistant K. pneumoniae isolates and investigate potential synergy between CFS and colistin. Methods: A total of 187 K. pneumoniae isolates were collected from hospitalized patients. Colistin resistance was determined using the broth microdilution method, identifying 25 colistin-resistant isolates (13.4%). Antimicrobial susceptibility was assessed using the Kirby-Bauer method. The antibacterial activity of selected Lactobacillus strains was evaluated using the agar-well diffusion method, while a modified Kirby-Bauer assay was used to assess the potential synergistic effect of colistin and CFS. Results: All 25 colistin-resistant isolates were multidrug-resistant (MDR), with 56% resistant to all tested antibiotics. Lactobacillus CFS exhibited significant antibacterial activity, with L. helveticus producing the largest inhibition zones, showing a statistically significant difference compared to other strains. However, rather than enhancing antibacterial activity, colistin reduced the inhibitory effects of Lactobacillus CFS against colistin-resistant K. pneumoniae. Conclusion: Lactobacillus CFS demonstrated significant antibacterial activity against colistin-resistant K. pneumoniae, highlighting its potential as a viable alternative antimicrobial approach. However, colistin did not enhance this effect, indicating a lack of synergy. Further in vivo studies are required to validate the clinical applicability of Lactobacillus in combating MDR-K. pneumoniae infections.